2021
DOI: 10.3390/ijms22157809
|View full text |Cite
|
Sign up to set email alerts
|

Complexome Profiling: Assembly and Remodeling of Protein Complexes

Abstract: Many proteins have been found to operate in a complex with various biomolecules such as proteins, nucleic acids, carbohydrates, or lipids. Protein complexes can be transient, stable or dynamic and their association is controlled under variable cellular conditions. Complexome profiling is a recently developed mass spectrometry-based method that combines mild separation techniques, native gel electrophoresis, and density gradient centrifugation with quantitative mass spectrometry to generate inventories of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 90 publications
(193 reference statements)
0
24
0
Order By: Relevance
“…Icons of the most popular tools used for CP studies are shown (see Section 2.1 for details). Protein abundance profiles are further obtained by (Continued ) Frontiers in Cell and Developmental Biology | www.frontiersin.org January 2022 | Volume 9 | Article 796128 intensity-based absolute quantification (iBAQ) (Schwanhausser et al, 2011;Tyanova et al, 2016a) et al (2014) and Wittig and Malacarne (2021). Ultimately, the list of hundreds or even thousands of identified proteins is mainly sorted based on similarities of the abundance patterns across fractions by hierarchical clustering analysis (Figure 1).…”
Section: General Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Icons of the most popular tools used for CP studies are shown (see Section 2.1 for details). Protein abundance profiles are further obtained by (Continued ) Frontiers in Cell and Developmental Biology | www.frontiersin.org January 2022 | Volume 9 | Article 796128 intensity-based absolute quantification (iBAQ) (Schwanhausser et al, 2011;Tyanova et al, 2016a) et al (2014) and Wittig and Malacarne (2021). Ultimately, the list of hundreds or even thousands of identified proteins is mainly sorted based on similarities of the abundance patterns across fractions by hierarchical clustering analysis (Figure 1).…”
Section: General Overviewmentioning
confidence: 99%
“…It is thus not surprising that the majority of CP studies use iBAQ since it enables a fair comparison between different protein groups in the same and multiple samples. Additional information regarding LFQ and other alternative methods have been reviewed in Fabre et al (2014) and Wittig and Malacarne (2021) . Ultimately, the list of hundreds or even thousands of identified proteins is mainly sorted based on similarities of the abundance patterns across fractions by hierarchical clustering analysis ( Figure 1 ).…”
Section: Complexome Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we report results from a complexome profiling analysis, in which high molecular weight protein complexes were separated using BN-PAGE, subsequently sliced into even fractions, and analyzed by quantitative mass spectrometry [ 60 , 61 , 62 ]. The identified proteins were quantified and their appearance in high molecular weight regions could be visualized as interaction profiles, using heatmaps [ 63 ]. Here, the comparison of the resulting profiles of two mitochondrial samples, from two different age stages of the P. anserina wild type, uncovered detailed age-dependent alterations of the mitochondrial complexome.…”
Section: Introductionmentioning
confidence: 99%